Pengaruh Kolonisasi Ganoderma spp. terhadap Pelapukan dan Viabilitas Miselium pada Tanaman Herbaceus - Rahmad Fadli; Suwandi Suwandi; Nurhayati Damiri (Vegetalika, 2026)
This study examines the effectiveness of Ganoderma sp. in decomposing lignin in herbaceous plants. The study was conducted in a greenhouse at the Faculty of Agriculture, Sriwijaya University, with temperatures ranging from 28-30oC and humidity reaching 70-80%. The test plants consisted of uwi (Dioscorea alata) and talas (Colocasia esculenta), and oil palm seedlings were used as a comparison. The parameters observed included the level of decay and mycelium viability after inoculation. The results showed that the highest level of decay occurred in taro, reaching 65.22% in sterilized soil and 52.56% in unsterilized soil, while uwi experienced decay of 33.9% and 33.03%. The viability of Ganoderma sp. mycelium remained high (>70%) in all treatments. This indicates a strong ability to adapt to various environmental conditions. Thus, the study shows that the ligninase activity of Ganoderma sp. contributes significantly to decomposition without reducing the viability of the Ganoderma sp.